2005
DOI: 10.1097/00126334-200501010-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Seroepidemiology of Human T-Lymphotropic Viruses

Abstract: Pregnant women better reflect the general population than blood donors or IDUs. The seroprevalence of HTLV-I and HTLV-II in Western Europe is 6-fold higher among pregnant women (4.4 per 10,000) than among blood donors (0.07 per 10,000). These data provide a robust baseline against which changes in HTLV-I and HTLV-II seroprevalence in Europe can be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…However, this comparison is likely to be inaccurate in view of the long time elapsed between the studies. In Europe, HTLV-1/2 prevalence was found to be 5–10 times higher in pregnant women than in blood donors, regardless of the area specific prevalence [17].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, this comparison is likely to be inaccurate in view of the long time elapsed between the studies. In Europe, HTLV-1/2 prevalence was found to be 5–10 times higher in pregnant women than in blood donors, regardless of the area specific prevalence [17].…”
Section: Discussionmentioning
confidence: 90%
“…Intermediate seroprevalence rates have been found in pregnant women. Although not devoid of bias, this group has been proposed to represent a more reliable portrait of the general population since their prevalence data are generally able to characterize geographic areas likely to be endemic [3], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates for HTLV-I and II were sixfold higher in pregnant women than in blood donors in the United Kingdom (Taylor et al, 2005). A study of 6754 pregnant women in Salvador, Brazil found 0.84% to be seropositive (Bittencourt et al, 2001).…”
Section: Phylogeny and Molecular Epidemiologymentioning
confidence: 99%
“…With HTLV-2 being less studied, estimations on the number of overall carriers is harder to make, but it has been estimated to be several million (4). In Central and Western Europe, the prevalence of HTLV-1, as well as HTLV-2, has been shown to be less than 0.1% among pregnant women and 0.005% among blood donors (20, 21). The prevalence of HTLV-1 is slightly higher in countries with high immigration from HTLV-1 endemic regions (mainly Portugal, Spain, France, UK) (22).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, higher frequencies of HTLV-2 have been described among PWID (around 3%) in Sweden (23), (around 10%) in Spain and Italy (12–14), and among HIV+ PWID (14.6%) in Ireland (15). In Eastern Europe, the data regarding the prevalences of HTLV-1 and HTLV-2 is largely absent except a single study from Romania where the prevalence of HTLV-1 was shown to be 0.053% among blood donors (20). …”
Section: Resultsmentioning
confidence: 99%